Pengaruh Pajak Restoran, Pajak Parkir, dan Pajak Air Tanah Terhadap Pendapatan Asli Daerah Kabupaten Wonogiri - Rika Rahmasari; Indra Lila Kusuma; Suprihati (Jurnal Pajak dan Analisis Ekonomi Syariah, 2025)
The analysis in this study aims to evaluate the influence of Restaurant Tax, Parking Tax, and Groundwater Tax on the Regional Original Revenue (PAD) of Wonogiri Regency. A quantitative method was applied in this research, utilizing historical data collected from the Regional Financial Management Agency (BPKD) of Wonogiri Regency for the 2020–2024 period. The results indicate that the Restaurant Tax does not have a significant effect on PAD, with a significance value of 0.204. In contrast, both the Parking Tax and Groundwater Tax have a positive and significant impact on PAD, with significance values of 0.001 and 0.007, respectively. These findings suggest that although the number of restaurants has increased, the demand for restaurant services has not kept pace. Meanwhile, the growth in motor vehicle numbers and public awareness of groundwater tax obligations have contributed to the increase in PAD. This study recommends enhancing the effectiveness of tax management and improving public outreach regarding tax obligations by the local government.